2020
DOI: 10.1016/j.ekir.2020.02.525
|View full text |Cite
|
Sign up to set email alerts
|

Sun-003 Online Hemodiafiltration (Post-Dilution) as Compared to High Flux Hemodialysis Does Not Improve Outcomes in Community Acquired Aki With sirs- A Randomised Controlled Trial

Abstract: Introduction: Contrast-induced nephropathy (CIN) / Contrast inducedacute kidney injury (CI-AKI) is one of the most common causes of hospital-acquired AKI. Methods: This is a prospective, single center study of 774 consecutive patients (449 males and 325 females with mean age of 48.85 AE 14.05 years) who underwent iodinated contrast procedures with nonionic, low-osmolality iodinated contrast medium (Iomeprol) via IV and IA routes from 2013 to 2015 were included in the study. CIN was defined as a relative increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In the 4 observational studies, quality varied, where 2 studies can be categorized as low quality [22, 29] and 2 as intermediate quality [1, 24] according to the Newcastle-Ottawa Scale. Overall, the risk of bias of all observational studies [1, 22, 24, 29] and 2 RCTs [23, 28] was high. Allocation concealment was not specified in most studies, which might induce a selection bias toward one modality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 4 observational studies, quality varied, where 2 studies can be categorized as low quality [22, 29] and 2 as intermediate quality [1, 24] according to the Newcastle-Ottawa Scale. Overall, the risk of bias of all observational studies [1, 22, 24, 29] and 2 RCTs [23, 28] was high. Allocation concealment was not specified in most studies, which might induce a selection bias toward one modality.…”
Section: Resultsmentioning
confidence: 99%
“…Dialysis prescription in terms of duration, blood flow rate, and dialysate flow rate varied across all studies, as shown in Table 1. Only one study [28] involved post-dilution HDF, while the remaining consisted of pre-dilution HDF or pre-dilution HF.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis comparing conventional HD to intermittent convective therapies, 15 we reported that only 3 small scale exploratory trials ever compared HD to HDF. 33 , 34 , 35 Most interestingly, pooling the results of these trials revealed a higher risk of in-hospital death with the use of HDF (Risk ratio: 2.07 CI: 1.04–4.11). 15 Therefore, further investigation was urgently required to determine the safety and potential benefits of HDF in an ICU setting.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, the possibility to perform high volume of convective clearance using IRRT is more recent with the development of online HDF. In a recent meta-analysis comparing conventional HD to intermittent convective therapies 15 , we reported that only 3 small scale exploratory trials ever compared HD to HDF [33][34][35] . Most interestingly, pooling the results of these trials revealed a higher risk of in-hospital death with the use of HDF (Risk ratio: 2.07 CI: 1.04-4.11) 15 .…”
Section: Discussionmentioning
confidence: 99%